Applied intelligence = Kecerdasan terapan / Robert J. Sternberg, James C. Kaufman, Elena L. Gregorenko ; alih bahasa, Yudi Santoso ; penyunting, Muhammadun. - STERNBERG, Robert J.; Kufman, James C.; Grigorenko, Elena L; Yudi Santoso; Muhammadun (Pustaka Pelajar, 2011)
xv, 590 hlm. : ilus. ; 23 cm (3 eks.)